Aging phenomena in non-crosslinked polyolefin blend cable insulation material: Electrical treeing and thermal aging - Lunzhi, Li; Jinghui, Gao; Lisheng, Zhong; Kai, Zhang; Xiaohan, Zhao (Frontiers in Chemistry, 2022)
Non-crosslinked polyolefin blends have become a favorable alternative material to crosslinked polyethylene (XLPE) cable insulation owing to their low power consumption in the production process and good recyclability at the end of service life. Although studies on non-crosslinked materials have achieved significant results, the electrical and thermal aging properties of these materials undeniably need extensive research attention and systematic exploration. Aging performance is directly related to the lifetime and reliability of cables. In this study, the electrical treeing and thermal aging phenomena of 70 wt.% linear low-density polyethylene (LLDPE) and 30 wt.% high-density polyethylene (HDPE) blends (abbreviated as 70L–30H) were studied and compared with those of XLPE by investigating the microstructural feature, electrical treeing behavior, and mechanical performance during thermal aging. Electrical treeing tests show that 70L–30H blends exhibited smaller treeing dimensions and lower electrical tree growth rates than those of XLPE. Thermal aging tests exhibit that the mechanical property degradation of 70L–30H blends is less than that of XLPE under the same aging time. Through differential scanning calorimetry analysis and microstructure observation, the 70L–30H blend shows higher melting temperature, thicker lamellae, and higher crystallinity with a uniform and fine spherulite structure, which are responsible for good anti-aging performance. This study indicates that the blends exhibit better electrical and thermal aging resistance than XLPE, which provides a performance guarantee for its further application in the non-crosslinked cable system.